Distributed Learning: Revitalizing Anesthesiology Training in Resource-Limited Ethiopia - Patel, Krupa B. (Front Public Health, 2017)
BACKGROUND: Ethiopia has a significant paucity of available health-care workers. Despite the increasing number of medical schools, there are not enough physician instructors. Furthermore, availability and standardization of postgraduate training are lacking. Modalities of e-learning have been shown to be successful when used to impart medical education in other resource-limited countries. The Emory University and Addis Ababa University (AAU) Departments of Anesthesiology have formed a collaboration with the intent of improving the AAU Anesthesiology residency program, one of two postgraduate training programs for anesthesiology in Ethiopia. METHODS: An initial educational needs assessment identified areas in the existing training program that required improvement. In this pilot study, we describe how the current classroom-based curriculum is augmented by the introduction of interactive educational sessions and distributed learning in the form of video lectures. Video lectures covered topics based on areas identified by Ethiopian residents and faculty. Interactive sessions included hands-on ultrasound workshops and epidural placement practicums, a journal club, problem-based learning sessions, and a mock code simulation. Assessment of the additions of the newly introduced blended learning technique was conducted via pre- and posttests on the topics presented. RESULTS: Pre- to posttest score averages increased from 54.5% to 83.6%. CONCLUSION: An expansion of educational resources and modes of didactics are needed to fill the gaps that exist in Ethiopian anesthesiology training. Incorporating distributed learning into the existing didactic structure may lead to more efficacious instruction resulting in a higher retention rate of information.